2012
DOI: 10.1186/1757-4749-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indole on drug resistance and virulence of Salmonella enterica serovar Typhimurium revealed by genome-wide analyses

Abstract: BackgroundMany Gram-positive and Gram-negative bacteria produce large quantities of indole as an intercellular signal in microbial communities. Indole demonstrated to affect gene expression in Escherichia coli as an intra-species signaling molecule. In contrast to E. coli, Salmonella does not produce indole because it does not harbor tnaA, which encodes the enzyme responsible for tryptophan metabolism. Our previous study demonstrated that E. coli-conditioned medium and indole induce expression of the AcrAB mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 66 publications
2
78
0
Order By: Relevance
“…The protective role of indole towards various stresses has been described in several microorganisms possibly through inducing efflux system or biofilm formation [31][32][33]. High level of extracellular indole was detected in E. coli in the stress condition of antibiotics treatment and supplementation or increase production of indole enhanced cell survival [10,13,14].…”
Section: Resultsmentioning
confidence: 97%
“…The protective role of indole towards various stresses has been described in several microorganisms possibly through inducing efflux system or biofilm formation [31][32][33]. High level of extracellular indole was detected in E. coli in the stress condition of antibiotics treatment and supplementation or increase production of indole enhanced cell survival [10,13,14].…”
Section: Resultsmentioning
confidence: 97%
“…Indeed, indole produced from just a few cells can protect a large population of E. coli against several antibiotics . Indole-regulated behaviours also extend to inter-species communication by affecting efflux-mediated multidrug resistance, flagella synthesis, virulence factor expression and host cell invasion by indole-non-producers like Salmonella enterica, Pseudomonas aeruginosa and even the yeast Candida albicans (Lee et al, 2009;Nikaido et al, 2011Nikaido et al, , 2012Oh et al, 2012;Raut et al, 2012). Finally, indole and other tryptophan-derived metabolites balance inflammation in the mammalian intestinal tract (Bansal et al, 2010;Keszthelyi et al, 2012;Nicholson et al, 2012) and strengthen the barrier function of epithelial tight junctions (Bansal et al, 2010;Keszthelyi et al, 2012;Nicholson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli can excrete considerable amounts of indole and acetate in the stationary phase (Helling et al, 2002;Kobayashi et al, 2006). Indole has received great attention because of its extensive effects on various biological functions in the bacterial population, such as biofilm formation, antibiotic resistance and virulence (Lee et al, 2007(Lee et al, , 2009Chu et al, 2012;Nikaido et al, 2012;Vega et al, 2012). Indole has been known to be exported by the AcrEF-TolC pump (Kawamura-Sato et al, 1999), although others have reported that indole freely diffuses across membranes and AcrEF was not required for indole export (Piñero-Fernandez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%